2016
DOI: 10.1115/1.4032544
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Energy Storage in Europe: Focus on Power to Fuel

Abstract: The energy sector in the European market has been changing significantly over the last years. European Union (EU) energy strategy includes the EU low-carbon roadmap milestone, which indicates for 2020, a 20% reduction in carbon emissions, and a 20% EU-wide share for renewables, and by 2030 a 40% reduction in carbon emissions and 30% EU-wide share for renewables. The increased renewable energy sources (RES) penetration and their intermittent energy production have led to the emerging need for energy storage tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…It is worth noting that the combination of CO 2 utilization and energy storage is realized under power‐to‐fuel technology (including power‐to‐gas and power‐to‐liquid), using renewable hydrogen. [ 38 ] Nowadays, methanol is one of the most effective commercial‐scale approaches for the transformation of CO 2 . It can be used for the production of several industrial chemicals, including formaldehyde, acetic acid, methyl tertiary‐butyl ether (MTBE), and dimethyl ether (DME).…”
Section: Current Status Of Co2 Utilizationmentioning
confidence: 99%
“…It is worth noting that the combination of CO 2 utilization and energy storage is realized under power‐to‐fuel technology (including power‐to‐gas and power‐to‐liquid), using renewable hydrogen. [ 38 ] Nowadays, methanol is one of the most effective commercial‐scale approaches for the transformation of CO 2 . It can be used for the production of several industrial chemicals, including formaldehyde, acetic acid, methyl tertiary‐butyl ether (MTBE), and dimethyl ether (DME).…”
Section: Current Status Of Co2 Utilizationmentioning
confidence: 99%
“…Additional technologies include compressed air and flywheels [6][7][8]. However, these solutions have drawbacks, such as a low energy density for batteries and high investment costs for pumped hydropower [9]. On the other hand, high energy density storage can be achieved by the so-called power to fuel technologies (PtF) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies discuss P2G systems based on water electrolysis, and this study mentions some of these studies. Reference [7] studied the techno-economics of P2G systems and concluded that these systems require subsides to overcome economic barriers. The study of [8] showed that an economic dispatch model involving wind power and a battery-energy storage system integrated with P2G helps to reduce the amount of wind power curtailment and stabilize fluctuations in the wind power output.…”
Section: Introductionmentioning
confidence: 99%